Krisis Modernitas dan Sains dalam Pandangan Seyyed Hossein Nasr - Faturohman, Ari Rizal (Jurnal Riset Agama, 2022)
This paper discusses the crisis conditions in modern times in the view of Seyyed Hossein Nasr. The method used in this research is literature study. The data analysis technique in this research is to collect references, read and conclude to present the findings in the form of descriptive data. The results of this study reveal that modern times in Nasr's view are inseparable from the development of human thought that occurred in the West. But in its development, science in the West has lost its transcendental reference. The existence of such circumstances resulted in several crises that hit mankind. The early events of human development are called the renaissance period. This period is also known as the period of human rebellion against God. The modern era, which has anthropocentric characteristics, always separates the contemplative and the action. The result is a tragedy that leads to a spiritual crisis, an environmental crisis and anxieties that plague human life.